تقدير الذات عند المراهق (مقاربة نفسية نظرية ) - غوافرية, رشيدة (جامعة الوادي - University of Eloued, 2019)
تعتبر مراهقة مرحلة انتقالية بين الطفولة وسن الرشد، وخلال هده المرحلة يحدث الكثير من التغيرات إنمائية السريعة تنعكس أثارها على مظاهر النمو الجسمي و الاجتماعي و الانفعالي و العقلي، ولا توجد فترة في الحياة الفرد أكثر أهمية بالنسبة لنمو الذات من المراهقة. إن المراهقة هي الوقت الذي يناضل فيه الفرد لكي يكون الشخص الذي يريده، فبناء تقدير الذات إيجابي يساهم في تطور الشخصية المراهق وبناء حياة ناجحة، وتحقيق التوافق السليم، كما يعتبر ومؤشرا دالا على الصحة النفسية والجسدية عند المراهق.The teenager is considerate as a transitional stage between childhood and the age of majority. During this stage, many rapid development changes are reflected in the physical, social, emotional and mental, There is no period in individual life more important for self-growth than adolescence. Adolescence is the time in which the individual struggles to be the person he wants. Building positive self-esteem contributes to the development of the adolescent personality, the building of a successful life, the achievement of proper Alignment, and the mental and physical health of the adolescent.
Self-Esteem in Adolescence (Psychological Approach)
مقال
Keywords: تقدير الذات ، المراهقة; Self esteem - adolescence